PEMANFAATAN CITRA SATELIT UNTUK PENENTUAN LAHAN KRITIS MANGROVE DI KECAMATAN TUGU, KOTA SEMARANG - Denny Maulana Ardiansyah; Imam Buchori (Geoplanning: Journal of Geomatics and Planning, 2014)
This study aims to map the level of the degraded land of mangrove forest area in TUGU Sub-district, Semarang, by comparing the results from the Landsat 7 ETM + images of 2009 and ALOS AVNIR-2 in 2009. To determine the degradation of mangrove forest area, we used geographic information systems-remote sensing as a tool of analysis based on three criteria; land use type, canopy density, and soil resilience from abrasion. The two satellite image data were used for supervised image classification using ER Mapper software to get the criteria of type of land use and density of the canopy. For soil resilience from abrasion, we utilized soil types reclassification techniques using ArcGIS software. Based on Landsat imagery, the results show that 92.22 % of the mangrove forest area is in severely damaged condition, and 7.78% is in the category of moderate damage. Meanwhile, based on the results of ALOS image, 77.73 % of the mangrove areas is in severely damaged condition, and 22.27 % is in the category of moderate damage. It can be concluded that ALOS and Landsat imageries are good for the determination of degraded mangrove land, especially in identifying its area and distribution in the mangrove forest. However, the degraded mangrove map generated by Landsat is less detailed than ALOS in classifying and representing the conditions of the degraded mangrove area in Tugu sub-district.